Transient measurement and structure analysis of protein–polysaccharide multilayers at fluid interfaces. Issue 31 (12th July 2019) - Bertsch, Pascal; Thoma, Alexandra; Bergfreund, Jotam; Geue, Thomas; Fischer, Peter
Abstract : Transient measurement of protein–polysaccharide multilayers at fluid interfaces: successive adsorption increases layer viscoelasticity, simultaneous adsorption impedes adsorption kinetics and layer strength. Abstract : The formation of electrostatic protein–polysaccharide multilayers has attracted attention for the design of fluid interfaces with enhanced stability and functionality. However, current techniques are often limited to measuring final multilayer properties. We present an interfacial shear rheology setup with simultaneous subphase exchange, allowing the transient measurement of biopolymer multilayers by their viscoelasticity. The successive and simultaneous adsorption of β-lactoglobulin (β-lg) and low-methoxyl pectin were investigated at the n -dodecane/water interface at pH 4. The successive injection of pectin increased the viscoelasticity of an adsorbed β-lg layer by electrostatic complexation. On the other hand, simultaneous adsorption impeded adsorption kinetics and interfacial layer strength due to complexation in the bulk phase prior to adsorption. Neutron reflectometry at the air–water interface confirmed the formation of an initial β-lg layer and electrostatic complexation of a secondary pectin layer, which desorbed upon pH-induced charge inversion. The layer formed by simultaneous adsorption mainly consisted of β-lg. We conclude that protein–polysaccharide complexes show limited surface activity and result in a lower effective protein concentration available for adsorption.